2020
DOI: 10.7861/clinmed.2020-0179
|View full text |Cite
|
Sign up to set email alerts
|

Prone positioning in conscious patients on medical wards: A review of the evidence and its relevance to patients with COVID-19 infection

Abstract: Medical teams continue to treat many patients with COVID-19 infection. This disease can result in profound hypoxaemia that may necessitate intubation and invasive mechanical ventilation in those who are critically ill. This intervention carries risk to both patients and healthcare workers and utilises significant hospital resource for prolonged periods. Simple, safe interventions that can be used before critical deterioration are highly desirable. The prone position in conscious non-ventilated patients with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
(38 reference statements)
1
24
0
6
Order By: Relevance
“…The benefit may result from the decrease of the anatomic dead space, reducing the ventilatory demand and work of breathing (WOB) [66]. In COVID-19, HFNC has been shown to be safe, well tolerated and it has a synergistic effect when combined with other treatments like prone position [67][68][69][70][71].…”
Section: Rationale Of Non-invasive Support In Arf Due To Sars-cov2: Hmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit may result from the decrease of the anatomic dead space, reducing the ventilatory demand and work of breathing (WOB) [66]. In COVID-19, HFNC has been shown to be safe, well tolerated and it has a synergistic effect when combined with other treatments like prone position [67][68][69][70][71].…”
Section: Rationale Of Non-invasive Support In Arf Due To Sars-cov2: Hmentioning
confidence: 99%
“…Some principles of prone position can be applied to awake extubated patients, but physiology is still not known in depth. It has been demonstrated as a safe intervention, and currently, it is widely used in emergency room, general wards as well as ICU settings [58,[68][69][70][71].…”
Section: Rationale Of Non-invasive Support In Arf Due To Sars-cov2: Hmentioning
confidence: 99%
“…5 High numbers of hospitalised patients develop respiratory symptoms, with reported incidence of over 80% of patients needing oxygen therapy. 6 , 7 Patients with increasingly severe COVID-19 symptoms may go on to develop acute respiratory failure and subsequently Acute Respiratory Distress Syndrome (ARDS). It has to be noted that these patients may not follow the typical ARDS disease trajectory.…”
Section: Respiratory Failurementioning
confidence: 99%
“…It has been found that it can delay and/or avert the need for intubation and mechanical ventilation. 7 , 28 The current pandemic has also revealed that this is a simple and safe intervention that is suitable for use on general wards.…”
Section: Conscious Prone Positionmentioning
confidence: 99%
“…Clinical experience, for example, suggested that non-invasive ventilation (NIV) has a role of primary importance in the management of CARDS as it can improve oxygenation, limiting the work of the respiratory muscles and preventing the onset of the patient self-inflicted lung injury (P-SILI) [2]. In this setting, adding the prone position to NIV could improve oxygenation, decrease respiratory effort, reducing self-induced lung injury, and avoid the need of intubation and invasive ventilation, which could be particularly useful in the case of reduced availability of intensive care unit (ICU) beds [4][5][6]. Nevertheless, as in CARDS there is often a rapid and sudden clinical worsening, which mainly affects the respiratory performance in terms of gas exchange, NIV can have serious limitations and not infrequently is it necessary to quickly resort to invasive mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%